Effects of forest bathing (Shinrin-yoku) in stressed people - Queirolo, Luca; Fazia, Teresa; Roccon, Andrea; Pistollato, Elisa; Gatti, Luigi; Bernardinelli, Luisa; Zanette, Gastone; Berrino, Franco (Frontiers in Psychology, 2024)
Aim: This study aims to explore the physiological effect of forest bathing on stress management.Methods: a total of 29 volunteers participated in this pre-post design, which lacked a control group. Several physiological parameters were recorded, including heart rate (HR), heart rate variability (HRV), electrodermal activity (EDA), blood pressure (BP), immunoglobulin A (IGA), salivary cortisol (sCort). Additionally, the perceived stress scale (PSS-10) was administered before forest exposure. Measurements were taken before and after participants spent two days fully immersed in a forest environment. To further assess stress management, participants underwent a Mental Arithmetic Task (MAT) before and after forest immersion, during which EDA, HRV and HR were monitored, using Empatica E4 wristband. Measurements were taken at baseline, during MAT and afterward (recovery).Results: Participants exhibited moderate perceived stress levels before forest immersion (mean PSS-10=21.22, SD 3.78). Post forest exposure, there was a significant decrease sCort (p<0.05) and e EDA (p<0.001), while HRV increased (p<0.001), and diastolic blood pressure rose (p<0.05). ANOVA results from the Mental Arithmetic Test (MAT) indicated that post immersion parasympathetic activity increased in all conditions compared to pre-exposure (p<0.05) except during recovery, while EDA decreased in all conditions post-forest exposure (p<0.05).Shinrin-yoku significantly improved stress management on a physiological level and could be a valuable resource for individuals experiencing stress. However, longitudinal studies with a control group are necessary to determine if these effects persist over time. This study nonetheless demonstrates the potential benefits of forest immersion for stress reduction by boosting our sympathovagal balance and the adaptability of our stress response system.